A Cognitive Linguistic Approach to Life Metaphor in Tetralogy Laskar Pelangi - Merry Lapasau; Sulis Setiawati (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
This study aims at finding the use of life metaphors in tetralogy Laskar Pelangi (hereinafter TLP). Data were analyzed in the framework of the Conceptual Metaphor Theory (CMT) by using a descriptive qualitative approach. We found 21 life metaphors in TLP and the finding shows that the conceptual metaphor of life as a target domain is mapped into several diverse source domains, and they are: life is a fluid in a container, life is a journey, life is a living organism, life is a precious possession, life is dedication to others, life is a struggle,life is guidance, life is war, and life is hard work. It can be concluded that TLP is rich with the use of metaphors in describing the cultural events of the Malays in detail. The way how the Malay master the problems in their lives, how they see and understand the world, is made clear by their language, which is reflected in conceptual metaphors. The results of this research support the idea that metaphors are not just rhetorical devices to say something more stylistically but they are conceptual in nature and its existence can be different in each culture.